Fodor's essential Turkey - Berkaya, Christine Drum; Hattam, Jennifer; Mataraci, Kevin; Nawdorny, Katie; Wallaya, Nora (Travel writer) (Fodor's travel guides., 2025)
"Fodor's Essential Turkey travel guide is packed with customizable itineraries with top recommendations, detailed maps of Turkey, and exclusive tips from locals. Whether you want to stroll through Istanbul's bazaars and mosques, explore Cappadocia's underground cities,or relax on the country's superb Mediterranean beaches, this up-to-date guidebook will help you plan it all out."--